SODIUM CHLORIDE POISONING IN IRAQI WATER BUFFALO (Bubalus bubalis) OF BASRAH GOVERNORATE, IRAQ - Al-Saad, K. M.; Alfaris, A. A.; Muhsen, R. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Sodium chloride poisoning has been suspected in Iraqi buffalo (Bubalus bubalis) of Basrah governorate, A study was conducted on 523 animals. All animals drank natural water from the Shatt al-Arab sources. Seventy-six animals show different clinical manifestations, and twelve clinically healthy animals were used as controls. Diseased buffalo exhibited different clinical manifestations. A significant increase in PCV with alterations in indices of clotting factors was also explored. Serum analysis demonstrated increase in serum sodium and chloride concentrations in diseased buffalo. However, water analysis revealed elevation of electrical conductivity, sodium, chloride and total dissolved solids in the drinking water of diseased buffalo. The macroscopic appearance of the carcasses showed congestion and slight edema of the brain tissues, Moreover, the histopathological examinations revealed, spongiform-like encephalopathy with severe congested blood vessels and neuro-vascular thrombus was detected.